Diversity and distribution of testate amoebae in freshwater ecoregions of Rio de Janeiro State, Brazil - Larissa Souza Monteiro; Karen Helena Costa Santos; Manoela dos Santos Moreira; Ana Caroline Quirino da Silva; Viviane Bernardes dos Santos Miranda; Christina Wyss Castelo Branco (Acta Limnologica Brasiliensia, 2025)
Abstract: Aim: Testate amoebae are a group that remains understudied. The present study conducted a survey on the testaceans’ records in several biotopes in ecoregions of the State of Rio de Janeiro, exploring differences in the occurrence of taxa. Methods A literature survey was carried out in the Scopus, Web of Science, Google Scholar and Scielo databases using the keywords in English and Portuguese "Testate Amoebae", "Thecamoebian", "Zooplankton" and accompanied by "Rio de Janeiro". Further, samples (collected by plankton mesh nets from 50 to 68 µm; bucket and bottle) from 12 locations were analyzed. The identification of taxa was conducted using an optical microscope with digital camera and Toup-View software for morphological measurements and with specific bibliography. All the records were georeferenced across the freshwater ecoregions of Rio de Janeiro. Statistical analyses were performed using R 4.3.3 Software (R Core Team 2024) through the Vegan package, a species accumulation curve (specaccum function), non-metric multidimensional scaling (nMDS) analysis based on ‘Jaccard’ dissimilarity and the PERMANOVA test performed. Results The bibliographic survey resulted in 35 publications from 1910 to 2023. The sum of records from the literature and from the samples analyzed comprised 37 localities and 250 taxa, including new records for the State of Rio de Janeiro. Centropyxis aculeata was the most frequent species (63.7%), and Difflugia, Centropyxis and Arcella were the most diverse genera. The species accumulation curve indicated that testaceans’ richness is underestimated, evidencing insufficient sampling. There was no significant difference between testaceans’ assemblages from different biotopes. Conclusions The records in Rio de Janeiro are underestimated due to insufficient sampling in some ecoregions. Future studies are needed to produce a taxonomic inventory more faithful real diversity.